The first occupation of cultural identity in ancient Kurdistan by the Obaids - Fattah, Dr. Othman Tafik; Sharif, L. Jaza Shorsh Hama (Sulaimani Journal for Humanities, 2025)
The first cultural conquest of ancient Kurdistan by the Obaids The Obaid culture is regarded as the first cultural phenomenon to arise in southern Mesopotamia following the retreat of the Arabian Gulf, which allowed land to emerge in the region. Each culture is uniquely shaped by its environment, and the Obaid culture subsequently spread from southern to northern Mesopotamia, influencing ancient Kurdistan. This expansion marked a historical "cultural invasion," as the dominant Halef culture in the southern and western parts of Kurdistan was replaced by Obaid culture, which characterized the southern regions. The Obaid culture transformed pottery-making techniques, incorporating regional influences that led to changes in decoration, particularly evident in the pottery from Northern Obaid. The paper explores the origins of the Obaid culture, its spread and impact on northern Mesopotamian cultures (Kurdistan), and the reciprocal influences between the two regions. Additionally, it examines the similarities and differences between southern and northern Obaid cultures, highlighting the extent to which Obaid culture influenced northern cultural practices